(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
This article examines the features of the labor market functioning in conditions of macroeconomic instability. It analyzes the key factors influencing the transformation of labor demand and supply, as well as the mechanisms of labor market adaptation to modern challenges, including digitalization and structural changes in the economy.